API solubility in semi-crystalline polymer: Kinetic and thermodynamic phase behavior of PVA-based solid dispersions - Mathers, Alex; Pechar, Matouš; Hassouna, Fatima; Fulem, Michal (International journal of pharmaceutics, 2022)
The formulation of amorphous solid dispersions (ASDs) represents a promising strategy for improving the poor bioavailability of many active pharmaceutical ingredients (APIs). The objective of this study was to investigate and compare the long-term physical stability (LTPS) of polyvinyl alcohol (PVA)-based solid dispersions formulated via hot-melt extrusion (HME) with their respective API-PVA temperature-composition (T-C) phase diagram. Furthermore, the impact of API glass-forming ability (GFA) on the LTPS was evaluated through the selection of two APIs with contrasting GFA (i.e., indomethacin (IND; good GFA) and naproxen (NAP; poor GFA)). Even though the predicted solubility of both APIs in PVA was less than 1 wt% at T = 25 °C, IND remained fully amorphous in HME-formulated IND-PVA extrudates with initial API loadings of 50, 40, and 30 wt% after a 24-month storage period. Meanwhile, NAP recrystallized to a considerable degree in each analogous sample with an amorphous NAP content of 22.5-23.5 wt% remaining after a 12-month storage period. While the constructed T-C phase diagrams were still in agreement with their respective LTPS study, they did not account for the impact of water uptake as well as potential HME-induced effects on the extrudate glass-transition temperature. This work may serve as a useful reference point for researchers who are interested in determining the solubility of an API in a semi-crystalline polymer and the challenges therein.
Keywords: polyvinylalkohol; příprava léků; polymery; termodynamika; farmaceutická chemie; Chemistry, Pharmaceutical; Amorphous solid dispersion; rozpustnost; Polymers; Thermodynamics; Glass-forming ability; Physical stability; Semi-crystalline polymer; Hot-melt extrusion; Polyvinyl Alcohol; Drug Compounding; Solubility